Algo Visualix: A Python-Based Algorithm Visualizer for Educational Enhancement - Sahu, Prince Kumar (International journal for research in applied science and engineering technology, 2025)
The Algo Visualix is an interactive tool that graphically demonstrates the step-by-step execution of algorithms, aiding students and developers in understanding complex computational processes. Built using Python, it offers real-time animations, user controls, and detailed explanations for sorting, searching, and graph traversal algorithms. This project enhances learning efficiency by bridging the gap between theory and implementation, with potential future improvements like AI-driven explanations and adaptive difficulty levels.